A COMMUNITY SURVEY ON THE PERFORMANCE OF THE PHILIPPINE NATIONAL POLICE (PNP) IN THE PROVINCE OF ALBAY - Deri, Ritzelda A.; Gilbas, Sherill A.; Dio, Ryan V. (International Journal of Research -GRANTHAALAYAH, 2021)
This paper highlights the trust, respect, safety and security ratings of the community to the Philippine National Police (PNP) in the Province of Albay. It presents the sectoral ratings to PNP programs. The survey utilized a structured interview with 200 sample respondents from Albay coming from different sectors. Male respondents outnumbered female respondents. The majority of the respondents are 41-50 years old, at least high school graduates and are married. The respondents gave the highest net rating on respect, followed by net rating on trust and the lowest net rating on safety and security on the performance of the PNP. Moreover, a high net rating on commitment of support to the identified programs of the PNP was also attained from the respondents. The highest net rating of support is given to the PNP’s anti-illegal drugs program, followed by anti-terrorism, anti-riding in tandem and anti-illegal gambling programs. The ratings of the PNP obtained from the different sectors of the community may be explained by the respondents’ nature of work or professions. Moreover, recommendations given by most of the respondents are focused on safety and security. The negative comments from the respondents may be considered to improve the PNP as an organization.